SMES in Russia: growth of indicators and contribution to the national economy ("Journal "U". Economy. Management. Finance.", 2025)
This article presents a study of the importance of the development of small and medium-sized enterprises for the Russian economy, and examines the areas of state support for business representatives, including national projects implemented in this field. The article also provides an assessment of the current state of business and its economic efficiency and contribution to the national economy.
Keywords: entrepreneurship; national economy; state support; national project